Measuring critical force in sport climbers: a validation study of the 4 min all-out test on finger flexors - Baláš, J.; Gajdošík, J.; Javorský, T.; Berta, P.; Feldmann, A. (European Journal of Applied Physiology, 2024)
Purpose The critical force (CF) concept, differentiating steady and non-steady state conditions, extends the critical power paradigm for sport climbing. This study aimed to validate CF for finger flexors derived from the 4 min all-out test as a boundary for the highest sustainable work intensity in sport climbers.